Modifications in the US Policy Concerning China in Terms of Controlling Access to Advanced Technologies Based on the Example of CHIPS and Science Act (Economic and Political Thought, 2023)
The article analyses modifications in American trade policy towards the PRCin the area of controlling access to advanced semiconductor technologies overthe last few years. Semiconductors are an extremely important technologythat underlies almost all modern industrial activities, especially those relatedto national security. This is the basis for other advanced emerging technologiesof the future. Tightening American control over access to semiconductortechnologies is one of the peaceful actions that can effectively slow downChina’s plans to become a global hegemon in the 21st century. This goal isachieved by the CHIPS and Science Act of 2022, which strengthens Americanproduction, supply chains and national security, and creates a fund that investsin research and development, science and technology, and the workforceof the future to regain leadership in semiconductor manufacturing.
Keywords: United States, PRC, semiconductors, microchips, trade policy, competition, security; United States, PRC, semiconductors, microchips, trade policy, competition, security; United States, PRC, semiconductors, microchips, trade policy, competition, security; United States, PRC, semiconductors, microchips, trade policy, competition, security; United States, PRC, semiconductors, microchips, trade policy, competition, security; United States, PRC, semiconductors, microchips, trade policy, competition, security; United States, PRC, semiconductors, microchips, trade policy, competition, security; United States, PRC, semiconductors, microchips, trade policy, competition, security; United States, PRC, semiconductors, microchips, trade policy, competition, security